2018
DOI: 10.3390/jof4030077
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungi: A Source of Potential Antifungal Compounds

Abstract: The emerging and reemerging forms of fungal infections encountered in the course of allogeneic bone marrow transplantations, cancer therapy, and organ transplants have necessitated the discovery of antifungal compounds with enhanced efficacy and better compatibility. A very limited number of antifungal compounds are in practice against the various forms of topical and systemic fungal infections. The trends of new antifungals being introduced into the market have remained insignificant while resistance towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 129 publications
(120 reference statements)
1
80
0
2
Order By: Relevance
“…Endophytic fungi have been studied as an alternative and sustainable means of converting the natural compounds in host plants to antifungal compounds, which are not only effective against human pathogens but also against phytopathogens [127]. Endophytic microorganisms are found in plant species of extreme importance [124] and can be classified as competent, optional, obligatory, opportunistic, or passive, depending on their effects on plants [128][129][130][131].…”
Section: Endophytic Fungi In Agriculturementioning
confidence: 99%
See 3 more Smart Citations
“…Endophytic fungi have been studied as an alternative and sustainable means of converting the natural compounds in host plants to antifungal compounds, which are not only effective against human pathogens but also against phytopathogens [127]. Endophytic microorganisms are found in plant species of extreme importance [124] and can be classified as competent, optional, obligatory, opportunistic, or passive, depending on their effects on plants [128][129][130][131].…”
Section: Endophytic Fungi In Agriculturementioning
confidence: 99%
“…Another beneficial approach involving endophytic fungi makes use of their production of bioactive secondary metabolites, which represent a group of microorganisms capable of synthesizing new compounds [138] that can target plant pathogens and pests [139]. Deshmukh et al (2018) reported several metabolites produced by endophytic fungi from medicinal plants and their potential as antifungal agents [127]. For example, scleroderma A and B and triterpenoid lanostane are produced by an endophyte basidiomycete fungus associated with the Eucalyptus grandis plant and these compounds were identified as potential fungicides against Candida albicans, C. tropicalis, C. crusei, and C. parapsiosis.…”
Section: Endophytic Fungi In Agriculturementioning
confidence: 99%
See 2 more Smart Citations
“…In general, fungal endophytes coexists asymptomatically with their hosts and they represent an underused group of microorganisms for the discovery of new valuable compounds because they can produce diverse metabolites and have the ability to synthesize substances that are only produced and isolated from higher plants [65]. In the same manner, the antioxidant activity of fungal endophytes from medicinal plants has gained recognition in natural product research during the last decades.…”
Section: Accumulation Of Phenolic Acids In Fungi Cell Wallsmentioning
confidence: 99%